Factors Associated with the Severity of Erythema Nodosum Leprosum Reactions - Anggraini, Ita; Esti, Prima Kartika; Komarasari, Eka (Journal of General - Procedural Dermatology and Venereology Indonesia, 2025)
Background: Leprosy is a chronic infection caused by Mycobacterium leprae. Leprosy reactions, including erythema nodosum leprosum (ENL), are induced by immune responses. ENL can cause neurological damage and deformities that result in disabilities. This study aimed to identify factors associated with the severity of ENL to help control the leprosy reactions. Methods: This was an analytical study on 148 patients with ENL reactions, who were divided into two groups based on the severity of their reactions. A retrospective cross–sectional study was conducted in the medical record unit of Sitanala Hospital, Tangerang, Banten, Indonesia, from May 2022 to April 2024. Data evaluated included age, gender, leprosy types, treatment status, duration of illness, clinical manifestations, involvement of other organs, disability, comorbidities, acid-fast bacilli, and laboratory examination. Categorical data was analyzed with chi-square test or Fisher’s exact test, and numerical data was analyzed with the Mann-Whitney test. Significance is determined at p < 0.05. Results: Characteristics including age, neuritis, skin ulcers, and comorbidities differ significantly between mild and severe ENL (p = 0.034; < 0.001; < 0.001; and 0.003, respectively). Severe ENL reactions tend to occur more frequently in older patients, and is associated with higher bacterial index (p = 0.004) and lower sodium and albumin levels (p = 0.014 and < 0.001, respectively). Conclusion: Age, neuritis, skin ulcer, comorbidities, bacterial index, as well as sodium and albumin levels were associated with the severity of ENL reactions. Appropriate management is required to prevent further complications.